Family Matters: Muslims in Sixteenth-Century Spanish America - Qamber, Rukhsana (Islamic Studies, 2021)
History has so far paid scant attention to Muslims in the earliest phase of colonizing the Americas. As a general policy, the Spanish Crown prohibited all non-Catholics from going to early Spanish America. Nevertheless, historians recognize that a few Muslims managed to secretly cross the Atlantic Ocean with the European settlers during the sixteenth century. Later they imported African Muslim slaves but historians considered both Africans and indigenous peoples passive participants in forming Latin American society until evidence refuted these erroneous views. Furthermore, the public had assumed that only single Spanish men went to the American unknown until historians challenged this view, and now women’s role is fully recognized in the colonizing enterprise. Additionally, despite the ban on non-Catholics, researchers found many Jews in the Americas, even if the Spanish Inquisition found out and killed almost all of them. In line with revisionist history, my research pioneers in three aspects. It demonstrates that Muslim men and women went to early Spanish America. Also, the Spanish Crown allowed Muslims to legally go to its American colonies. Additionally, the documents substantiate my new findings that Muslims went to sixteenth-century Latin America as complete families. They mostly proceeded out of Spain as the wards or servant-slaves of Spanish settlers after superficially converting to Catholicism. The present study follows two case studies that record Muslim families in early sixteenth-century Spanish America. Paradoxically, their very persecutor—the Spanish Church and its terrible Inquisitorial arm—established their contested belief in Islam.